Propuesta para la implementacion de un modelo de integración para capacidad tecnológica (MICT), para las empresas del sector metalmecanico del cantón Queevdo, provincia de los Ríos, año 2014 - Camacho Parraga, Jonny Patricio (2015)
In Recent years have the technological capacity Will Become a cornerstone for the growth of small and mainly Economies technological Those That Changes the industries are more sensitive electronics Such as, systems, biotechnology, medicine, are The most representative cases, other areas however we are no strangers to Changes of the different new technologies and structure of the production system and how to organize a company. Innovation strategy is to Develop That Helps us the resources of enterprises, so it Helps in supporting business Competitiveness. Engineering industries That do not have any adequate monitoring in terms of technological surveillance, UNLIKE other companies That If They take and use monitoring tool east Properly, will generate Disadvantages Compared to these. The objective of east research was to Develop a model for improvement based on the integration model for technological capacity (MICT), for companies in the metalworking industry of Canton Quevedo, east objective was to Achieve Characterized and EVALUATED the process in metal mechanical companies, with Which production lines are based. Elements and technological resources Processes Involved in Establishingmechanisms for analysis and development strategies of technological capability based on the use of indicators was Identified